Deuteronomy between Pentateuch and the Deuteronomistic history - Seters, John van (HTS teologiese studies, 2003)
The problem of how Deuteronomy relates to the Pentateuch and to the book of Joshua came to the fore with Noth’s thesis of a Deuteronomistic History, which was in conflict with the earlier support for a Hexateuch in the Documentary Hypothesis. With the current decline of the Documentary Hypothesis, one approach is to give greater emphasis to Pentateuchal and Hexateuchal redactors, often in place of the J and P sources, which either use Deuteronomy to conclude the Pentateuch or to build a bridge to the Deuteronomistic History. An alternative view, expressed in this paper, rejects the notion of such redactors and sees J and P as later than, and supplementary to, the Deuteronomistic History. To support this view, the article will examine Eckart Otto’s Pentateuchal redactor in Deuteronomy 4, at parallel texts in Numbers and Deuteronomy, and at Pentateuchal and Hexateuchal redactors in Deuteronomy 34 and Joshua 24.